NEW NON-MARINE OSTRACOD GENERA AND SPECIES OF APTIAN AGE FROM ARARIPE BASIN, NORTHEAST BRAZIL - Almeida-Lima, Débora Soares De; Guzmán, Juliana; Maia, Renata Juliana Arruda; Sousa, Ariany De Jesus E; Piovesan, Enelise Katia (Zootaxa, 2024)
The Ostracoda Subclass comprises the most expressive group of calcareous microfossils in the deposits of the Araripe Basin, especially in its post-rift sequence, which is represented by the Santana Group, of Late Aptian age (= Alagoas Local Stage). Due to the abundance, ostracod species are of great importance for understanding the evolution of the Araripe Basin, with direct application in biostratigraphic and paleoecological analyses. Improving these important applications involves refining the taxonomy of these ostracods, which also contributes to understanding the diversity of this fauna. Increasing knowledge about the ostracod group, this paper describes new and rare taxa recovered from outcrop and well core samples from the Araripe Basin. Two new genera are proposed, Batecypris gen. nov. and Macunhaella gen. nov., and five new species Batecypris reticularis sp. nov., Macunhaella posteroaltis sp. nov., Timiriasevia aratra sp. nov., Theriosynoecum favus sp. nov. and Wolburgiopsis magnafossa sp. nov.. These five taxa were assigned to the families Cyprididae Baird, 1845 and Limnocytheridae Klie, 1938, which comprise other important and known genera for the Araripe Basin. This study shows that in the Araripe Basin the mentioned families can be more diverse than already known, adding value to the understanding of the pre-salt section deposition.